2022
DOI: 10.21203/rs.3.rs-2255985/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Online Speech Assessment of the Psychotic Spectrum: Exploring the relationship between overlapping acoustic markers of Schizotypy, Depression and Anxiety.

Abstract: Background Remote assessment of acoustic alterations in speech holds promise to increase scalability and validity in research across the psychosis spectrum. A feasible first step in establishing a procedure for online assessments is to assess acoustic alterations in psychometric schizotypy. However, to date, the complex relationship between alterations in speech related to schizotypy and those related to comorbid conditions such as symptoms of depression and anxiety has not been investigated. This study teste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…Testing the usability of these measures in online settings with short speech samples would complement the work presented here. Furthermore, whilst our study focused on text-based language markers, numerous findings support the use of vocal, acoustic markers to assess psychotic symptoms from speech [10,[42][43][44], which were not included here. Other findings suggest the potential of other, remotely assessable markers coming from visual cues or passive sensing data of smart devices for monitoring or assessment [10,[42][43][44][45][46][47].…”
Section: Limitations and Further Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…Testing the usability of these measures in online settings with short speech samples would complement the work presented here. Furthermore, whilst our study focused on text-based language markers, numerous findings support the use of vocal, acoustic markers to assess psychotic symptoms from speech [10,[42][43][44], which were not included here. Other findings suggest the potential of other, remotely assessable markers coming from visual cues or passive sensing data of smart devices for monitoring or assessment [10,[42][43][44][45][46][47].…”
Section: Limitations and Further Researchmentioning
confidence: 99%
“…Furthermore, whilst our study focused on text-based language markers, numerous findings support the use of vocal, acoustic markers to assess psychotic symptoms from speech [10,[42][43][44], which were not included here. Other findings suggest the potential of other, remotely assessable markers coming from visual cues or passive sensing data of smart devices for monitoring or assessment [10,[42][43][44][45][46][47]. Testing these markers in online settings, especially in additive nature to text-based markers would be another important step to potentially improve the power and precision of automated, online assessment of the psychotic spectrum.…”
Section: Limitations and Further Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, studies have demonstrated that individuals with high schizotypy exhibit alterations in acoustic features of speech like reduced speech variability, expressiveness and atypical pitch patterns compared to those with lower schizotypy scores (20,67). In remotely collected speech samples, schizotypy scores were positively associated with acoustic features like Mel frequency cepstral coefficients (MFCC), loudness parameters, Hammerberg -index, Spectral flux, and slope measures (68)(69)(70), where changes in loudness parameters were uniquely associated with schizotypy (compared to features associated with anxiety and depression symptoms). Importantly, analytical and modelling approaches that have been used to discriminate clinical psychosis from healthy controls could be successfully applied to discriminate between low and high level of schizotypy, reaching 69-88% of accuracy (68)(69)(70).…”
Section: Speech Techniques and Analysis Applied In Subclinical Popula...mentioning
confidence: 99%
“…In remotely collected speech samples, schizotypy scores were positively associated with acoustic features like Mel frequency cepstral coefficients (MFCC), loudness parameters, Hammerberg -index, Spectral flux, and slope measures (68)(69)(70), where changes in loudness parameters were uniquely associated with schizotypy (compared to features associated with anxiety and depression symptoms). Importantly, analytical and modelling approaches that have been used to discriminate clinical psychosis from healthy controls could be successfully applied to discriminate between low and high level of schizotypy, reaching 69-88% of accuracy (68)(69)(70). These findings suggest that speech analysis techniques hold promise in capturing subtle speech abnormalities associated with subclinical psychotic symptoms.…”
Section: Speech Techniques and Analysis Applied In Subclinical Popula...mentioning
confidence: 99%